Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Keputusan Investasi Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderating - Adam Bangkit Arsyada; Sukirman Sukirman; Indah Fajarini Sri Wahyuningrum (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to determine the influence of company size, profitability, and investment decisions on the value of the company by presenting the capital structure as a moderation variable. This study used the population of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Sampling techniques using Purposive Sampling techniques using the criteria of food and beverage sub-sector manufacturing companies listed consecutively on the Indonesia Stock Exchange from the period from 2017-2019 so that as many as 24 samples of companies with the number of analysis units as many as 72. The method used in this study is regression moderation analysis with interaction tests. Secondary data in the form of financial statements used in this study. The IBM SPSS Statistics 21 application is used as an analysis tool. Results from research show that the size of the company, and profitability have a significant effect on the value of the company. Investment decisions have no significant effect on the value of the company. The capital structure is also unable to moderate significantly the influence of the size of the company on the value of the company. But the capital structure can significantly moderate profitability and investment decisions to the value of the company. Suggestions for researchers can further increase or replace the sample of companies in other sectors. In addition, it can also add other variables that can affect the value of the company, so it is expected that research into the value of the company continues to grow.